2017
DOI: 10.1039/c7cc02335a
|View full text |Cite
|
Sign up to set email alerts
|

Donor ligands based on tricoordinate boron formed by B–H-activation of bis(phosphine)boronium salts

Abstract: We report a novel method for the preparation of PBP-pincer complexes from bis(phosphine)boronium salts. The central (RP)HB-moiety in a palladium complex is demonstrated to be a L-type ligand, therewith completing a series of pincer-type complexes with Z-, X- and L-type boron-based ligands, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…[14,15] Therelated borylene complexes X and 1, which can be regarded as aN HC-supported phosphonium bora-ylides,have been prepared independently by Braunscheweig et al and our group (Scheme 1). [14,18] However,tothe best of our knowledge, their use as p-donating substituents to stabilize electron deficient species has not yet been described, although the substituent effect of boryl groups,a se xtremely strong sdonors,o nt he properties of divalent species of group 14 elements has been well studied by Aldridge et al [19] Therefore,w ec onsidered the synthesis of ah eterocyclic silylene (type C)f eaturing ab oron-based p-donating substituent. [14,18] However,tothe best of our knowledge, their use as p-donating substituents to stabilize electron deficient species has not yet been described, although the substituent effect of boryl groups,a se xtremely strong sdonors,o nt he properties of divalent species of group 14 elements has been well studied by Aldridge et al [19] Therefore,w ec onsidered the synthesis of ah eterocyclic silylene (type C)f eaturing ab oron-based p-donating substituent.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[14,15] Therelated borylene complexes X and 1, which can be regarded as aN HC-supported phosphonium bora-ylides,have been prepared independently by Braunscheweig et al and our group (Scheme 1). [14,18] However,tothe best of our knowledge, their use as p-donating substituents to stabilize electron deficient species has not yet been described, although the substituent effect of boryl groups,a se xtremely strong sdonors,o nt he properties of divalent species of group 14 elements has been well studied by Aldridge et al [19] Therefore,w ec onsidered the synthesis of ah eterocyclic silylene (type C)f eaturing ab oron-based p-donating substituent. [14,18] However,tothe best of our knowledge, their use as p-donating substituents to stabilize electron deficient species has not yet been described, although the substituent effect of boryl groups,a se xtremely strong sdonors,o nt he properties of divalent species of group 14 elements has been well studied by Aldridge et al [19] Therefore,w ec onsidered the synthesis of ah eterocyclic silylene (type C)f eaturing ab oron-based p-donating substituent.…”
mentioning
confidence: 99%
“…[16,17] Of particular interest, these boron species,b eing isoelectronic with amines,p resent an ucleophilic three-coordinate boron center with al one-pair, [13,14] and it has been clearly demonstrated that they can be used as s-donating ligands for transition metals. [14,18] However,tothe best of our knowledge, their use as p-donating substituents to stabilize electron deficient species has not yet been described, although the substituent effect of boryl groups,a se xtremely strong sdonors,o nt he properties of divalent species of group 14 elements has been well studied by Aldridge et al [19] Therefore,w ec onsidered the synthesis of ah eterocyclic silylene (type C)f eaturing ab oron-based p-donating substituent. In this case,one can expect amore effective electron donation to the silylene center compare to amino and phosphonium-(ylide) groups (A and B)since boron and silicon present very similar electronegativities (2.0 and 1.9, respectively).…”
mentioning
confidence: 99%
“…As previously noted, borylenes are not likely to be sufficiently stabilized by tertiaryp hosphines to allow for their isolation, [11] butthese specieshave been reported as ligandscoordinated to at ransition metal. [12,13,18,19] In the case of aluminum(I), the situation is different:a lthought he FeÀAl interaction is rathers trong, the AlH fragment as ac oordinated ligand is not sufficiently stabilized by tertiary phosphine substituents.H owever,w ith carbenes as stabilizing substituents, iron complexes containing ligand-stabilized aluminum(I) as ad onor ligand can be isolated. [20] Moreover,o ur findings show that, for X = BH, CH, and C, the bond in thesec omplexes can be interpreted as ad onor-acceptor bond from the phosphines to the central group, whichi tself acts as an electron-donatingl igand.…”
Section: Eda-nocv Results Of Iron Complexes 2a-dmentioning
confidence: 99%
“…[11] Nonetheless,i ti sp ossible to stabilizes uch species embedded as donor groups in pincertype ligands, such as in the iron(II)c omplex 1a Ph (Figure 1). [12,13] Based on structural parameters, spectroscopic properties, natural bond orbital( NBO) analyses, and topological studies based on the quantum theory of atomsi nm olecules (QTAIM), it was shownt hat the tricoordinated boron atom in 1a Ph served as an electron-donatingl igand ( Figure 1). As ac onsequence, the central donorg roup is best described as ap hosphine-stabilized borylene.…”
Section: Introductionmentioning
confidence: 99%
“…However, with more weakly bound substituents and less steric shielding the isolation of these ligand‐stabilized borylenes (L 2 RB) is often difficult. [ 77 ] Nonetheless, transition metal complexes containing neutral donor ligands based on tri‐coordinate boron are accessible by B–H‐oxidative addition of stabilized boronium salts ( 13 , Scheme 7), [ 78–83 ] in an analogous way with respect to the oxidative addition of boranes to boryl ligands (Scheme 4). The resulting ligands in complexes of similar to 14 are best described as neutral pincer‐type ligands containing three L‐type functions.…”
Section: Coordination Patterns With Non‐metal Ligating Atomsmentioning
confidence: 99%